EFEKTIFITAS LAGU DALAM PROGRAM PENGURANGAN RESIKO BENCANA GEMPA BUMI SISWA PAUD RA. AL-MUNAWWAROH LEMBANG: THE EFFECTIVENESS OF THE SONG IN THE EARTHQUAKE DISASTER RISK REDUCTION PROGRAM OF PAUD RA STUDENTS. AL-MUNAWWAROH LEMBANG - Maria; Untung Sudharmono (Jurnal Kesehatan, 2023)
The Lembang Fault causes cracks along 29 kilometers, the Lembang Fault which crosses 5 districts starting from the districts of Lembang, Parongpong, Cisarua, Ngamprah and Padalarang Lembang which has the potential for earthquakes of 6.8 SR. The purpose of this study was to measure the effectiveness of songs in earthquake risk reduction programs for Paud RA. Al-Munawwaroh students Lembang. This research method uses quantitative descriptive, data taken through observation of the behavior of PAUD RA students. AL-Munawwaroh Lembang. The respondents in this study were 31 students, The research instrument used observation sheets to document the behavior of PAUD students. Disaster material is delivered through disaster song lyrics sung at the beginning of each class will start for one week. The simulation is carried out by blowing a whistle indicating an earthquake. During the simulation, researchers observed and documented the behavior of Paud RA. Al-Munawwaroh students Lembang, Lembang, West Bandung Regency on the observation sheet. The results of the study found that 80.6% of PAUD students followed instructions to save themselves from the classroom during an earthquake, so it was hoped that students could survive when an earthquake occurred. The conclusion of this study is that the delivery of disaster material through song lyrics sung every day can be used for earthquake risk reduction programs for Paud RA. Al-Munawwaroh students Lembang